Memori Kultural dalam Puisi-Puisi Taufiq Ismail: Keluarga, Kampung Halaman, dan Kampus - Fajar, Yusri (Faculty of Humanities, Diponegoro University, 2024)
This article investigates the cultural memory depicted in the poems of Taufiq Ismail in his book Tirani dan Benteng. Extensive research has been conducted on the social and political themes, nature and environmental aspects, and intrinsic elements in Ismail's poems. Hence, this essay will specifically examine how Ismail portrays cultural memories in the speaker’s poem, pertaining to his personal and societal experiences that have engulfed his life both in the past and today. The researcher uses the theory of cultural memory to scrutinize the poems. Data collection is conducted using document study. The researcher engages in meticulous examination, carefully chooses and categorizes the poems from the volume of Tirani dan Benteng that align with the specific emphasis of the cultural memory issues, and subsequently analyzes them using the content analysis approach. The research findings revealed that three poems by Ismail Taufiq, including Potret Keluarga, Jam Kota, and Alma Mater, shed light on the speaker and evoked his memories of his family, hometown, and campus. Taufik Ismail effectively accentuates the reimagination of collective memories through the utilization of familial objects, the surrounding landscape, the development of the city, and historical university buildings. The cultural memory that initially surfaced from the individual's memory point to a shared (cultural) memory that links to a social bond with family members, significant historical events in the hometown, and the nexus with other students during their study at the university.